Using Competitive Intelligence in Fashion Industry Analysis - Bortnik, Svitlana; Černý, Jan; Molnár, Zdeněk, 1939-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2023)
The master thesis aims to explore the application of competitive intelligence in the analysis of the US fashion industry. Competitive intelligence plays a crucial role in informing strategic decision-making and maintaining a competitive edge in the dynamic and highly competitive fashion sector. The study explores the significance and value of competitive intelligence, investigates theoretical concepts and methodologies, and evaluates the practical implementation of competitive intelligence techniques using industry-specific tools and technologies. The findings contribute to understanding the importance of competitive intelligence, provide insights into its theoretical foundations, and offer practical implications for effectively applying competitive intelligence in the US fashion industry.
Vedoucí práce: Jan Černý
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: information systems management [obor dipl. práce]; diplomové práce; master's theses